Designing real-world laboratories for the reduction of residential energy use. Articulating Theories of Change. - Heiskanen, Eva; Laakso, Senja; Matschoss, Kaisa; Backhaus, Julia; Goggins, Gary; Vadovics, Edina (Oekom, 2018)
Real-world laboratories (RwLs) hold potential for transdisciplinary research that considers the context of changing households' energy practices. Taking into account stakeholders' understandings of what would work where, how and why helps to recognize the contextual conditions for the transferability of RwL results. Reducing residential energy use and carbon dioxide emissions is a policy concern across Europe. One of the approaches to address this problem, real-world laboratories (RwLs), has recently gained prominence as a means to generate both sustainability change and social knowledge. Yet RwLs are context-bound, and transferability is an issue for scaling up change. Drawing on Realistic Evaluation (RE) and Theories of Change (ToC), this paper analyses researchers' and practitioners' views on the role of contexts and change mechanisms in the outcomes of interventions targeting residential energy use. The results show that extracting the underlying logic of RwL designs could help to identify where and when these designs are likely to be transferrable. This contribution has implications for the design of future RwLs, given that RwLs have until now rarely articulated their ToC.
Keywords: Nachhaltige Entwicklung; Wohnen; Privathaushalt; Energieverbrauch; Heizung; Wissenstransfer; Reallabor; Forschungsmethode; Projekt; Internationaler Vergleich